Codesign of the Population Health Information Management System to measure reach and practice change of childhood obesity programs - Amanda M Green; Christine Innes-Hughes; Chris Rissel; Jo Mitchell; Andrew J Milat; Mandy Williams; Lina Persson; Sarah Thackway; Nicola Lewis; John Wiggers (Sax Institute, 2018)
Introduction: Childhood obesity prevalence is an issue of international public health concern and governments have a significant role to play in its reduction. The Healthy Children Initiative (HCI) has been delivered in New South Wales (NSW), Australia, since 2011 to support implementation of childhood obesity prevention programs at scale. Consequently, a system to support local implementation and data collection, analysis and reporting at local and state levels was necessary. The Population Health Information Management System (PHIMS) was developed to meet this need. Design and development: A collaborative and iterative process was applied to the design and development of the system. The process comprised identifying technical requirements, building system infrastructure, delivering training, deploying the system and implementing quality measures. Use of PHIMS: Implementation of PHIMS resulted in rapid data retrieval and reporting against agreed performance measures for the HCI. The system has 150 users who account for the monitoring and reporting of more than 6000 HCI intervention sites (early childhood services and primary schools). Lessons learnt: Developing and implementing PHIMS presented a number of complexities including: applying an information technology (IT) development methodology to a traditional health promotion setting; data access and confidentiality issues; and managing system development and deployment to intended timelines and budget. PHIMS was successfully codesigned as a flexible, scalable and sustainable IT solution that supports state-wide HCI program implementation, monitoring and reporting.